Using Mapping Pivotal as Teaching Moral Education Material and Historical Meaning in Banten Literature - Nurhaedah Gailea (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The objective of this study is to obtain appropriate learning materials of character education using Mapping Pivotal Table in Banten Literature. This research is a qualitative research through content analysis method. The data is taken from Banten Legend; “Legend of Kiai Gede”, “Nyai Bansari”, “The Seven Wells”, and key informant with expert. In analyzing the data, the researcher used character table by Bohlin’s theory (2013) that consist of moral starting point, 1st morally pivotal point, 2nd morally pivotal point, challenge point, and new change. The result of this research showed that Banten Legends contain moral educational values. The moral educational values are religious, hard worker, patriotism, never give up, responsibility, sincerity, caring other people and mutual respect (Solehat & Ramadan, 2021). The result found a close relationship between the stories with historical of Banten. “The seven Wells” are location in Serang-Banten and people believed that they brought God’s mercy for women life. And women who want to get married are advised to bathe in the water of the seven wells so that it brings blessings for a new life. The early time to be Pandeglang or the regency is known well as the place of religious men which found in the explanation of the legend of Kiai Gede. And Nyai Bansari showed Banten women are smart and brave who fight for the independence of their nation (Murhandono and Juwono 2014).